Self-Schemas and Self-Esteem Discrepancies in Subclinical Paranoia: The Essential Role of Depressive Symptoms - Monsonet, Manel; Ballespí, Sergi; Sheinbaum, Tamara; Valiente, Carmen; Espinosa, Regina; Kwapil, Thomas Richard; Barrantes-Vidal, Neus (Frontiers in Psychiatry, 2021)
Background: Self-concepts are being intensively investigated in relation to paranoia, but research has shown some contradictory findings. Studying subclinical phenomena in a non-clinical population should allow for a clearer understanding given that clinical confounding factors are avoided. We explored self-esteem, self-schemas, and implicit/explicit self-esteem discrepancies in 3 non-clinical groups with different psychopathological traits and a control group. Methods: Participants with elevated trait-paranoia (n=41), depressive symptoms (n=34), a combination of both traits (n=32), and a control group (n=71) were assessed on implicit and explicit self-esteem, self-schemas, depression, and paranoia. A dimensional approach with the total sample (n=208) was also used to complement the information provided by the group approach. Results: All groups presented similar and positive levels of implicit self-esteem. Trait-paranoia participants had similar levels of explicit self-esteem and self-schemas compared to the control group. However, the group with a combination of trait-paranoia and depressive symptoms showed the lowest levels of positive self-schemas and self-esteem. Furthermore, this group and the control group displayed implicit/explicit self-esteem discrepancies, although in opposite directions and with different implications. The dimensional approach revealed associations of trait-paranoia and depressive symptoms with poor explicit self-esteem and self-schemas, but not with implicit self-esteem. Conclusions: Trait-paranoia participants showed different self-representations depending on whether depressive symptoms were present or not. The interaction between subclinical neurotic and psychotic traits entailed a worse self-representation that might increase the risk for psychopathology.